KEKUATAN BIOREMEDIASI JAMUR DAN BIOKONVERSI LIMBAH PERTANIAN MENGGUNAKAN TEKNOLOGI BUDIDAYA JAMUR - Sabaruddin Wagiman Tjokrokusumo (Jurnal Teknologi Lingkungan, 2007)
Bioconversion technology of agricultural waste or biowaste has beenknown by industries as one of the technology that could provide orincrease quality og fod through industrial food processing. However,some of people in Indonesia have not been realized that uneconomicvalues and unnutritious of agro materials could be converted into highvalue of food and feed, and also usefull material for soil conditionerwhich is improved soil health. In addition, spent mushroom substrateas a waste of mushroom production can be used for a stater material toremediate contaminated soil as one of the strong capability materialfor bioremediation technology for polluted environment. Therefore, thisreview would like to create some hopes for pheasant to covert someagricultural waste materials into useful materials toward povertyalleviation and sustainable community development as mentioned bymillennium development goals. Through this application ofbioconversion and bioremediation technology of agricultural waste whichis ubicuitous in tropical countries like Indonesia, we do much more forenvironmental care and social welfare.